Integrin β3 Deficiency Results in Hypertriglyceridemia via Disrupting LPL (Lipoprotein Lipase) Secretion. Issue 5 (May 2020) - Xiao, Bing; Mao, Jianhua; Sun, Boyang; Zhang, Wei; Wang, Yun; Wang, Pengran; Ruan, Zheng; Xi, Wenda; Li, Huiyuan; Zhou, Jingyi; Lu, Yide; Ding, Qiulan; et al.
Abstract : Objective: Integrin β3 is implicated in numerous biological processes such as its relevance to blood triglyceride, yet whether β3 deficiency affects this metabolic process remains unknown. Approach and Results: We showed that the Chinese patients with β3-deficient Glanzmann thrombasthenia had a 2-fold higher serum triglyceride level together with a lower serum LPL (lipoprotein lipase) level than those with an αIIb deficiency or healthy subjects. The β3 knockout mice recapitulated these phenotypic features. The elevated plasma triglyceride level was due to impaired LPL-mediated triglyceride clearance caused by a disrupted LPL secretion. Further analysis revealed that β3 directly bound LPL via a juxtamembrane TIH (threonine isoleucine histidine) 720 –722 motif in its cytoplasmic domain and functioned as an adaptor protein by interacting with LPL and PKD (protein kinase D) to form the PKD/β3/LPL complex that is required for β3-mediated LPL secretion. Furthermore, the impaired triglyceride clearance in β3 knockout mice could be corrected by adeno-associated virus serotype 9 (AAV9)-mediated delivery of wild-type but not TIH 720– 722 -mutated β3 genes. Conclusions: This study reveals a hypertriglyceridemia in both β3-deficient Chinese patients and mice and provides novel insights into the molecular mechanisms of the significant roles of β3 in LPL secretion and triglyceride metabolism, drawing attention to the metabolic consequences in patients with β3-deficient Glanzmann thrombasthenia. Abstract : Supplemental Digital Content is available in the text.